REPRESENTASI REKAYASA SOSIAL SEBAGAI SARANA KEADILAN HUKUM - Kusumawati, Yayuk (SANGAJI: Jurnal Pemikiran Syariah dan Hukum, 2017)
In the social life, there is circulation life which change quickly and slowly, so the system of law in Indonesia should be adjusted unnamed conservative. To answer that challenge, needed the social engineering in the social life to fulfill their goals. Social engineering presented to solve problem in social life. Principle, fungtion of the low to be able to change the symbol or method in social life, it can make the habitual become strong or more loyalited and may be the other habitual which happen in social life. That condition, such as deleted the habitual which not match to social need or create new habitual which though more benefit and kindness than before. Refer to the dynamic social circulation, the changing is a necessary. In this term, fungtion of the low must be maximalized for justice and peace, it is mean to social wealth